2012
DOI: 10.1096/fj.12-221325
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cerebral ischemia‐reperfusion injury with PEGylated liposomes encapsulating FK506

Abstract: FK506 (Tacrolimus) has the potential to decrease cerebral ischemia-reperfusion injury. However, the clinical trial of FK506 as a neuroprotectant failed due to adverse side effects. This present study aimed to conduct the selective delivery of FK506 to damaged regions, while at the same time reducing the dosage of FK506, by using a liposomal drug delivery system. First, the cytoprotective effect of polyethylene glycol-modified liposomes encapsulating FK506 (FK506-liposomes) on neuron-like pheochromocytoma PC12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 34 publications
4
56
0
Order By: Relevance
“…Cerebral ischemia causes a broad spectrum of pathophysiologic changes, including blood-brain barrier disruptions and increased vascular permeability: the enhanced permeability and retention effect. Previous studies have shown that an increase in vascular permeability by ischemia may enable selective targeting of drugs at the critical site of action, allowing effective drug delivery to the ischemic hemisphere of the brain (14,15). Our results of g imaging by 99m Tc-HMPAO (supplemental materials) clearly demonstrated liposomal accumulation in the ischemic hemisphere of the brain.…”
Section: Discussionsupporting
confidence: 61%
“…Cerebral ischemia causes a broad spectrum of pathophysiologic changes, including blood-brain barrier disruptions and increased vascular permeability: the enhanced permeability and retention effect. Previous studies have shown that an increase in vascular permeability by ischemia may enable selective targeting of drugs at the critical site of action, allowing effective drug delivery to the ischemic hemisphere of the brain (14,15). Our results of g imaging by 99m Tc-HMPAO (supplemental materials) clearly demonstrated liposomal accumulation in the ischemic hemisphere of the brain.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, when liposomes were associated with contrast agents, researchers observed that they quickly accumulated in the ischemic zone. 134,143,148,152,190 Some formulations have demonstrated their ability to improve in vivo activity of drugs, such as chrysophanol, 133 dexamethasone phosphate, 154 nerve growth factor, 170 Xe, 150,158 FK506, 149 isopropylidene-shikimic acid, 151 asialo-erythropoietin, 153 antisense oligonucleotides, 165 plasmids, 174 quercetin, 166,168 fasudil, 176 nitric oxide, 146 N-acetylleucyl-leucyl-norleucine amide, 178 and a combination of synergistic drugs. 156,175 Very recently, a promising uncoupling new drug -ZL006 (5-(3, 5-dichloro-2-hydroxybenzylamino)-2-hydroxybenzoic acid) -was developed for stroke treatment.…”
Section: Stroke or Cerebral Ischemiamentioning
confidence: 99%
“…Conventional liposomes are rapidly removed from circulation by the reticuloendothelial system (RES), which leads to fast systemic elimination. The circulation time can be extended by decreasing the particle size (<100 nm) and by liposome-surface modification with polyethylene glycol (PEG) [14]. Pegylation allows these liposomes, named Stealth ® liposomes, to escape from mononuclear phagocyte system and to extend blood-circulation time [15].…”
Section: Lipids and Cationic Lipidsmentioning
confidence: 99%